Microstrip Bandpass Filter With Tunable Notch Response At 5.2 GHz Using Defected Microstrip Structure - Mutalib, Mohamad Ariffin; Zakaria, Zahriladha; Shairi, Noor Azwan (Research India Publications, 2016)
-